The prevalence of latex sensitisation and allergy and associated risk factors among healthcare workers using hypoallergenic latex gloves at King Edward VIII Hospital, KwaZulu-Natal South Africa: a cross-sectional study - Shumani Makwarela Phaswana; Saloshni Naidoo (BMJ Open)
Objectives The present study describes latex sensitisation and allergy prevalence and associated factors among healthcare workers using hypoallergenic latex gloves at King Edward VIII Hospital in KwaZulu-Natal, South Africa.Design Cross-sectional study.Setting A tertiary hospital in eThekwini municipality, KwaZulu-Natal, South Africa.Participants 600 healthcare workers were randomly selected and 501 (337 exposed and 164 unexposed) participated. Participants who were pregnant, with less than 1 year of work as a healthcare worker and a history of anaphylactic reaction were excluded from the study.Primary and secondary outcome measures Latex sensitisation and latex allergy were the outcome of interest and they were successfully measured.Results The prevalence of latex sensitisation and allergy was observed among exposed workers (7.1% and 5.9%) and unexposed workers (3.1% and 1.8%). Work-related allergy symptoms were significantly higher in exposed workers (40.9%, p<0.05). Duration of employment was inversely associated with latex allergy (OR 0.9; 95% CI 0.8 to 0.9). The risk of latex sensitisation (OR 4.2; 95% CI 1.2 to 14.1) and allergy (OR 5.1; 95% CI 1.2 to 21.2) increased with the exclusive use of powder-free latex gloves. A dose–response relationship was observed for powdered latex gloves (OR 1.1; 95% CI 1.0 to 1.2). Atopy (OR 1.5; 95% CI 0.7 to 3.3 and OR 1.4; 95% CI 0.6 to 3.2) and fruit allergy (OR 2.3; 95% CI 0.8 to 6.7 and OR 3.1; 95% CI 1.1 to 9.2) also increased the risk of latex sensitisation and allergy.Conclusions This study adds to previous findings that healthcare workers exposed to hypoallergenic latex gloves are at risk for developing latex sensitisation highlighting its importance as an occupational hazard in healthcare. More research is needed to identify the most cost effective way of implementing a latex-free environment in resource-limited countries, such as South Africa. In addition more cohort analysis is required to better understand the chronicity of illness and disability associated with latex allergy.